Etiological Value of Sterile Inflammation in Preeclampsia: Is It a Non-Infectious Pregnancy Complication? - Banerjee, Sayani; Huang, Zheping; Wang, Zhengke; Nakashima, Akitoshi; Saito, Shigeru; Sharma, Surendra; Cheng, Shibin (Frontiers in Cellular and Infection Microbiology, 2021)
Understanding of sterile inflammation and its associated biological triggers and diseases is still at the elementary stage. This becomes more warranted in cases where infections are not associated with the pathology. Detrimental effects of bacterial and viral infections on the immune responses at the maternal-fetal interface as well as pregnancy outcome have been well documented. However, an infection-induced etiology is not thought to be a major contributing component to severe pregnancy complications such as preeclampsia (PE) and gestational diabetes. What are the upstream triggers for local and systemic inflammation in these pregnancy complications? Moreover, it is not clear what type of inflammation is involved in the onset of PE-like features. We opine that sterile inflammation regulated by the inflammasome-gasdermins-caspase-1 axis is a contributory factor to the onset of PE. We hypothesize that increased production and release of damage-associated molecular patterns (DAMPs) or Alarmins such as high-mobility group box1 (HMGB1), cell-free fetal DNA, uric acid, the NOD-like receptor pyrin-containing receptor 3 (NLRP3) inflammasome, IL-1 and IL-18 occur in the PE placenta. Some of these molecules have already been observed in the placenta from women with PE. Mechanistically, emerging evidence has demonstrated that excessive placental endoplasmic reticulum (ER) stress, impaired autophagy and gasdermine D (GSDMD)-mediated intrinsic pyroptosis are key events that contribute to local and systemic sterile inflammation in patients with PE, especially early-onset PE (e-PE). In this review, we highlight the advances on the roles of sterile inflammation and inflammatory signaling cascades involving ER stress, autophagy deficiency and pyroptosis in PE pathophysiology. Deciphering the mechanisms underlying these inflammatory pathways may provide potential diagnostic biomarkers and facilitate the development of therapeutic strategies to treat this devastating disease.